Avaliação da Sobrecarga Salina na Complacência Arterial em Animais Espontaneamente Hipertensos - Roza, Thais Luma de Oliveira (2021)
The interaction between BP and sodium intake is widely recognized and supported by numerous studies. More recently, clinical studies have shown a close relationship between increased arterial stiffness (as measured by the gold standard VOP choice) and sal